Citizen's income and welfare regimes in Latin America :from cash transfers to rights - Lo Vuolo, Rubén M. (Palgrave Macmillan, 2013)
"Social protection systems in Latin America developed in a fragmented manner, offering varying access to benefits and benefit levels to population groups. In the context of widespread informal and precarious work, social insurance institutions could only provide limited coverage. In this context, progress towards a Citizen's Income policy in Latin America depends on the possibility of reappraising its importance for an integrated institutional system, which promotes the empowerment and economic independence of the people. A Citizen's Income policy is not only a cash transfer to alleviate poverty or a basic income for food. It is a basic right to improve democracy and encourage a more autonomous development of people living in profoundly unequal societies"--